Anatomy and Development of Khon Kaen 60-3, Kaset 1 and Tainan 9 Peanut Seed Coat - Wasu Amaritsut; Juangjun Duangpatra; Tiamjai Komkris (Agriculture and Natural Resources, 1994)
A study on anatomical structure of wrinkleness peanut seed coat in the two large-seeded peanut varieties, Khon Kaen 60-3 and Kaset 1 and one small-seeded variety, Tainan 9 revealed that the two large-seeded varieties were higher in percentages of wrinkled seed than Tainan 9. Seed coat thickness and seed moisture content decreased as the peanut seeds approached maturity. Wrinkled seed coats were thinner than the non-wrinkled seed coats. Wrinkleness of peanut seed coat was found to have been caused by the curvature of the seed coat surface along the vascular bundles while the non-wrinkled one had smooth seed coat surface. The curvature of the seed coat resulted in the more external surface area of the wrinkled seed.